NAMPT-mediated NAD+ biosynthesis suppresses activation of hepatic stellate cells and protects against CCl4-induced liver fibrosis in mice. (December 2021) - Xu, Lin; Yang, Chenyan; Ma, Jie; Zhang, Xinge; Wang, Qingzhi; Xiong, Xiwen
Background: Nicotinamide phosphoribosyltransferase (NAMPT) catalyzes the rate-limiting step in the salvage pathway of mammalian nicotinamide adenine dinucleotide (NAD + ) biosynthesis. Through its NAD + -biosynthetic activity, NAMPT is able to regulate the development of hepatic steatosis and inflammation induced by diet or alcohol. However, the roles NAMPT plays in the development of liver fibrosis remain obscure. Purpose: To investigate the roles of NAMPT-mediated NAD +  biosynthesis in hepatic stellate cell (HSC) activation and liver fibrosis. Research Design: Realtime RT-PCR and western blot analyses were performed to analyze the expression of profibrogenic genes. Sirius red staining was conducted to examine the fibrosis in liver. Mouse liver fibrosis was induced by intraperitoneal injection of carbon tetrachloride (CCl4 ) 2 times a week for 6 weeks. Adenovirus-mediated NAMPT overexpression or nicotinamide mononucleotide (NMN) administration was carried out to study the effects of elevation of NAD +  levels on protecting CCl4 -induced liver fibrosis in mice. LX2 cells or primary HSCs were used to study the role of NAMPT overexpression or NMN treatment in reducing profibrogenic gene expression in vitro. Results CCl4  administration suppresses NAMPT expression in liver and reduces hepatic NAD +  content. Tgfβ1 treatment decreases intracellular NAD +  levels and NAMPT expression in LX2 cells. Adenovirus-mediated NAMPT overexpression augments liver NAD +  levels, inhibits HSC activation and alleviates CCl4 -induced liver fibrosis in mice. Administration of NMN also suppresses HSC activation and protects against CCl4 -induced liver fibrosis in mice. Conclusions: NAMPT-mediated NAD +  biosynthesis inhibits HSC activation and protects against CCl4 -induced liver fibrosis.